Thesis and dissertation writing in a second language : - Paltridge, Brian (Routledge, 2007)
The relationship of supervisor to student has traditionally been seen as one of apprenticeship, in which much learning is tacit, with the expectation that the student will become much like the tutor. The changing demographics of higher education in conjunction with imperatives of greater accountability and support for research students have rendered this scenario both less likely and less desirable and unfortunately many supervisors are challenged by the task of guiding non-native speaker students to completion. This handbook is the ideal guide for all supervisors working with undergraduate and postgraduate non-native speaker students writing a thesis or dissertation in English as it explicitly unpacks thesis writing, using language that is accessible to research supervisors from any discipline.